THE FEATURES OF THE CONSTRUCTION OF THE FOCAL MECHANISMS OF LOCAL EARTHQUAKES USING THE EXAMPLE OF AN EVENT NEAR BEREGOVO 23.11.2006 - Malytskyy, D.; Hrytsai, O.; Muyla, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The features of the construction of the focal mechanisms for earthquakes in the Carpathian region is researched. Principle and features of the construction of the focal mechanism using graphic method are considered. Focal mechanism is built for earthquake, occurred 23.11.2006 near Beregovo, using this method. The constructed mechanism using graphical method is compared with the mechanism, which is built using complex of programs.